Risk Factors Associated with Plantar Necrosis following Tarsal Arthrodesis in Dogs - Holroyd, Kate L.; Meeson, Richard L.; Pead, Matthew J.; Mukherjee, Lachlan; Ferguson, John F.; Kulendra, Elvin (Veterinary and Comparative Orthopaedics and Traumatology, 2023)
Objectives The aim of this study was to define landmarks of the intermetatarsal channel of the dorsal pedal artery and to assess whether damage to the dorsal pedal artery during metatarsal screw placement in dogs undergoing pan- and partial-tarsal arthrodesis (PanTA/ParTA) could be a mechanism in the development of plantar necrosis.Study Design This study was divided in to two parts: (1) ex-vivo anatomical study: 19 canine cadavers, (2) retrospective clinical study: 39 dogs. Cadaveric dissection documented the mean intermetatarsal channel position. Metatarsal screw position was evaluated on postoperative radiographs of dogs after PanTA or ParTA. Screw position, arthrodesis type and surgical approach were assessed for their impact on complications, including plantar necrosis.Results The mean proximal and distal extent of the intermetatarsal channel lies between 4.3% ± 1.9 and 22.8% ± 2.9 the length of metatarsal III (MTIII) respectively. The intermetatarsal channel lies within the most proximal 25% of MTIII in 95% of cases. At least one screw risked damaging the mean intermetatarsal channel position in 92% of dogs; 8% of these dogs went on to develop plantar necrosis. The mean screw position did not differ between ParTA cases with or without plantar necrosis (p > 0.05).Conclusion Violation of the intermetatarsal channel is possible during metatarsal screw placement. Care should be taken when placing screws in the proximal 25% of the metatarsals, specifically avoiding exiting dorsally between MTII and MTIII and across the distal region of the intermetatarsal channel, where the perforating metatarsal artery passes interosseously, as damage may contribute to the aetiology of plantar necrosis.
Keywords: plantar necrosis; arthrodesis; perforating metatarsal artery; intermetatarsal channel; pantarsal